The Role of Physical Activity in Reducing Inflammation: Implications for Preventive Medicine - Justyna Weronika Kmieć; Piotr Kulej; Justyna Woźniak; Wiktor Biesiada; Anna-Mariia Chernysh; Aleksandra Dusińska; Jakub Waszczyński; Kamila Fuczyło; Karolina Stankevič (Quality in Sport)
Physical activity is an accessible and free, modifiable factor which influences our health and wellbeing. Increased physical activity (PA) and exercise are associated with reduced chronic disease risk. The prevalence of physical inactivity is constantly increasing. Physical inactivity is associated with the development of various chronic diseases including cancer, cardiovascular, metabolic and neurodegenerative diseases [1].